Ro 44-9883, a New Non-Peptidic GPIIb-GPIIIa Antagonist Prevents Platelet Loss in a Guinea Pig Model of Extracorporeal Circulation - Carteaux, Jean-P; Steiner, Beat; Roux, Sébastien (Thrombosis and Haemostasis, 1993)
Extensive contact between blood and artificial surfaces causes platelet activation and depletion. The aim of the present study was to test the efficacy of Ro 44-9883, a potent and selective peptidomimetic GPIIb-IIIa antagonist, in preventing platelet loss in guinea pigs undergoing extracorporeal circulation (ECC) with bubble oxygenation. In 15 guinea pigs, an arterio-arterial shunt was created and perfused for 1 h from the aortic arch to the descending aorta. The guinea pigs were divided into three groups: A control group receiving only heparin as an i.v. bolus, a low dose-treated group and a high dose-treated group receiving in addition to heparin and before starting ECC, 1 or 7 mg/kg Ro 449883 as an i.v. bolus, respectively. In the control group, the platelet count at 30 and 60 min of ECC was dramatically decreased (35 ± 4% and 25 ± 3% of initial value). In the low dose-treated group, Ro 44-9883 partially prevented the drop in platelet count (69 ± 8% and 54 ± 9%; p <0.05) whereas in the high dose-treated group, the platelet count was normal at 30 min (97 ± 8%) and only slightly decreased at 60 min (80 ± 7%). Mean arterial pressure and hematocrit were not significantly different between groups during the experiment. We conclude that i) ECC in guinea pigs provides an interesting in-vivo model for studying platelet loss by contact activation and ii) Ro 44-9883 prevents platelet loss during ECC in a dose dependent manner.